ROMANTISME SEBAGAI BENTUK ESTETIKA DALAM NOVEL HILMY MILAN KARYA NADIA RISTIVANI - Cindi Syaharani; Sri Wahono Saptomo; Sukarno (Fakultas Bahasa dan Sastra Universitas PGRI Kanjuruhan Malang, 2024)
This research aims to describe romanticism as a form of aesthetics in the novel Hilmy Milan by Nadia Ristivani. The problem discussed in this research is how the novel Hilmy Milan by Nadia Ristivani actualizes romanticism as a form of aesthetics. This research method uses a descriptive qualitative method with a literature study technique. The data is in the form of quotations that contain meaning about romanticism. The data source in this research is a novel entitled